Anatomic variations of the gastrocolic trunk of Henle and implications for colon surgery (Annals of Medical Research, 2025)
Aim: Henle’s trunk is a crucial venous structure involved in the drainage of veins originating from the stomach, colon, and the pancreas. Variations in the formation of the trunk exist and it can have significant clinical implications, particularly in procedures involving lymphadenectomy and vessel ligation around this location. In this study, we aimed to demonstrate variations in the venous architecture of the Henle’s trunk with the use of CT images.Materials and Methods: In this retrospective study, 287 patients who had 3D CT imaging for different purposes in a single institution between January 2018 and June 2022 were evaluated. Patients were grouped into two groups as gastrocolic trunk and gastropancreaticocolic trunk based on the presence of a pancreatic branch contributing to the formation of Henle’s trunk. Variations in these two groups were retrospectively evaluated.Results: Variations of the Henle’s trunk are classified as bipod, tripod, or tetrapod. In our series (n=287), the most common subclassification of the gastrocolic trunk was a bipod which included right gastroepiploic vein and right colic vein (n=36, 12.5%). The most common subclassification of the gastropancreaticocolic trunk was a tripod which included right gastroepiploic vein, right colic vein, and anterior superior pancreaticoduodenal vein (n=80, 60.6%).Conclusion: A thorough examination of the right colon vascular anatomy requires an understanding of venous variations of the Henle’s trunk. These variations highlight the importance of individualized assessments for patients, especially those undergoing right hemicolectomy and gastrectomy. This knowledge will aid in reducing surgical complications and improving oncologic outcomes.
Keywords: Gastrocolic trunk; Gastropancreaticocolic trunk; Henle’s trunk; Colon cancer; Gastric cancer